2015
DOI: 10.1080/16184742.2015.1021824
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of sport development event legacy: an examination of the Australian Surf Life Saving Championships

Abstract: Research question: This study explores whether the conduct of an unleveraged major event, the Australian Surf Life Saving Championships, leaves a legacy in terms of making a contribution towards the ongoing sport development of surf life-saving. This is an area of event legacy research that has received little empirical research. Research methods: Secondary data sources from the event host organisation were used as indicators of sport development. Regression analysis, adjusting for changes in the outcome varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 47 publications
0
9
0
3
Order By: Relevance
“…Fourth, as we focused on residents' perceptions in defining and measuring the event's impacts, it is desirable to supplement the current findings with more objective evidence. For example, in relation to the theme of sport, health, and well-being, Hodgetts and Duncan (2015) assessed the Australian Surf Life Saving Championships' impact on local sport participation by analyzing secondary data on membership and competitor numbers. One challenge of adopting designs similar to Hodgetts and Duncan's study is to gather comprehensive secondary data sources that capture various impacts identified in the current research.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Fourth, as we focused on residents' perceptions in defining and measuring the event's impacts, it is desirable to supplement the current findings with more objective evidence. For example, in relation to the theme of sport, health, and well-being, Hodgetts and Duncan (2015) assessed the Australian Surf Life Saving Championships' impact on local sport participation by analyzing secondary data on membership and competitor numbers. One challenge of adopting designs similar to Hodgetts and Duncan's study is to gather comprehensive secondary data sources that capture various impacts identified in the current research.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Notwithstanding its prevalence in policy and political discourse, a large amount of the literature supporting the trickle-down effect is based on anecdotal evidence with very few studies examining population-level data (Brown & Massey, 2001;Murphy & Bauman, 2007;Weed et al, 2009). The quantitative studies that have been completed have provided little evidence of sustained sport participation increases as a result of the trickle-down effect (Hanstad & Skille, 2010;Hodgetts & Duncan, 2015;Murphy & Bauman, 2007;Veal & Frawley, 2009;Weed et al, 2015;Wicker & Sotiriadou, 2013), with only a few examples of a positive association (Potwarka, 2015;Potwarka & Leatherdale, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Small and medium spectator events show mixed results as to whether or not the event had stimulated sport participation, as two studies concluded that the event under investigation had positively impacted sport participation (i.e., Ramchandani and Coleman, 2012 ; Ramchandani et al, 2015 ), while three studies concluded that the event had no impact on sport participation (i.e., Taks et al, 2014 ; Hodgetts and Duncan, 2015 ; Misener et al, 2015b ). Interestingly, six of the studies found mixed results in that there was not enough evidence to support a claim of increased participation or there was increased participation among certain populations and no changes in participation among others (i.e., Taks et al, 2013 , 2015 , 2018 ; Derom and VanWynsberghe, 2015 ; Misener, 2015 ; Hoskyn et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%